Hypercapnia: clinical relevance and mechanisms of action. Issue 1 (February 2015) - Masterson, Claire; Otulakowski, Gail; Kavanagh, Brian P.
Abstract : Purpose of review: Multiple clinical and laboratory studies have been conducted to illustrate the effects of hypercapnia in a range of injuries, and to understand the mechanisms underlying these effects. The aim of this review is to highlight and interpret information obtained from these recent reports and discuss how they may inform the clinical context. Recent findings: In the last decade, several important articles have addressed key elements of how carbon dioxide interacts in critical illness states. Among them the most important insights relate to how hypercapnia affects critical illness and include the effects and mechanisms of carbon dioxide in pulmonary hypertension, infection, inflammation, diaphragm dysfunction, and cerebral ischemia. In addition, we discuss molecular insights that apply to multiple aspects of critical illness. Summary: Experiments involving hypercapnia have covered a wide range of illness models with varying degrees of success. It is becoming evident that deliberate hypercapnia in the clinical setting should seldom be used, except wherever necessitated to avoid ventilator-associated lung injury. A more complete understanding of the molecular mechanisms must be established.